2015
DOI: 10.1016/j.csl.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Fully automated assessment of the severity of Parkinson's disease from speech

Abstract: For several decades now, there has been sporadic interest in automatically characterizing the speech impairment due to Parkinson’s disease (PD). Most early studies were confined to quantifying a few speech features that were easy to compute. More recent studies have adopted a machine learning approach where a large number of potential features are extracted and the models are learned automatically from the data. In the same vein, here we characterize the disease using a relatively large cohort of 168 subjects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 21 publications
0
47
0
3
Order By: Relevance
“…Per-utterance features are based on F0 jitter, shimmer, harmonic to noise ratio (HNR), and the energy ratio of the first and second harmonics (H12). In previous work, we found that these features detect voiced segments and estimate F0 more accurately than other algorithms and that they are useful in rating the severity of a subjects Parkinsons disease [16]. Jitter and shimmer (and, of course, F0) have been used previously for emotion detection (e.g., [17]); however, few if any studies on emotion detection have used the harmonic model or have used it for estimating F0, jitter, or shimmer.…”
Section: Hm Features: Features Based On the Harmonic Modelmentioning
confidence: 97%
“…Per-utterance features are based on F0 jitter, shimmer, harmonic to noise ratio (HNR), and the energy ratio of the first and second harmonics (H12). In previous work, we found that these features detect voiced segments and estimate F0 more accurately than other algorithms and that they are useful in rating the severity of a subjects Parkinsons disease [16]. Jitter and shimmer (and, of course, F0) have been used previously for emotion detection (e.g., [17]); however, few if any studies on emotion detection have used the harmonic model or have used it for estimating F0, jitter, or shimmer.…”
Section: Hm Features: Features Based On the Harmonic Modelmentioning
confidence: 97%
“…In previous work, we found that these features detect voiced segments and estimate pitch frequency more accurately than other algorithms and that they are useful in rating the severity of subjects' Parkinsons dis ease [25]. work [23].…”
Section: Speech Features From Harmonic Modelmentioning
confidence: 98%
“…Moreover, given the estimate of unknown parameters, we reconstruct noise-free signal and compute other pitch-related features such as Harmonic-to-Noise Ratio (HNR), shimmer, and jitter. We refer the reader to our recent works [16] [17] for more detail on extracting aforementioned features from harmonic model.…”
Section: Speech Features From Harmonic Modelmentioning
confidence: 99%